Capacity development as a research domain: frameworks, approaches, and analytics - Babu, Suresh Chandra; Sengupta, Debdatta (International Food Policy Research Institute, 2006)
Strengthening national capacity for designing public policies and program interventions is fundamental for achieving development goals. Yet results of capacity strengthening programs have shown mixed results in the last fifty years. Capacity development, as a field of scientific enquirty still lacks a unified framework among development professionals. Capacity development is defined as the process by which individuals, groups, organizations, institutions, and societies increase their ability to perform core functions, solve problems, define and achieve objectives, and understand and sustainably deal with development issues. The concept of capacity as an integral component of development agendas is not new, yet it has only recently been acknowledged that development plans and goals cannot be achieved without adequate local capacity. Increased attention to the lack of capacity and the absence of relevant institutions has brought to light their importance in the successful design, implementation, and evaluation of development plans, programs, and policies. Despite this now common wisdom, research-based information on how to strengthen institutions and institutional capacity in developing countries is severely lacking. This paper attempts to review the emerging theories, frameworks, approaches, and analytics of capacity development. After developing a rationale for capacity development research, it presents potential research themes. Arguing for a new economics of capacity development, it concludes with some possible impacts of considering capacity strengthening as a research domain.